2015
DOI: 10.1007/s11427-012-4336-5
|View full text |Cite
|
Sign up to set email alerts
|

The genetic architecture of autism spectrum disorders (ASDs) and the potential importance of common regulatory genetic variants

Abstract: Currently, there is great interest in identifying genetic variants that contribute to the risk of developing autism spectrum disorders (ASDs), due in part to recent increases in the frequency of diagnosis of these disorders worldwide. While there is nearly universal agreement that ASDs are complex diseases, with multiple genetic and environmental contributing factors, there is less agreement concerning the relative importance of common vs rare genetic variants in ASD liability. Recent observations that rare mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
(79 reference statements)
0
5
0
Order By: Relevance
“…CNVs are believed to originate via diverse mutational mechanisms such as errors in replication, meiotic recombination, and repair of double-strand breaks [2]. Evidence has mounted that CNVs make a significant contribution to rare variants involved in rare diseases [3][4][5][6] and more common diseases such as cancers [7,8] and neurodevelopmental disorders [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…CNVs are believed to originate via diverse mutational mechanisms such as errors in replication, meiotic recombination, and repair of double-strand breaks [2]. Evidence has mounted that CNVs make a significant contribution to rare variants involved in rare diseases [3][4][5][6] and more common diseases such as cancers [7,8] and neurodevelopmental disorders [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, polygenic risk scores encompassing ASD, schizophrenia, and years of educational attainment have been recently shown to be unambiguously associated with ASD and to also contribute to the phenotype in the cases of patients carrying de novo deleterious mutations [16]. The second pattern of genetic variants contributing to ASD reflects the effect of rare, highly penetrant mutations or CNVs that are inherited or, more frequently, arise de novo in the germinal cells; being affected by negative selection because of their detrimental impact on reproductive fitness, their frequency in the general population remains very low [22]. Given the described difficulties in pinpointing common variants related to its onset, progress in ASD genetic research has so far advanced mainly with the discovery of rare, de novo, germline, coding, heterozygous mutations.…”
Section: Genetic Causes Of Autism: Rare and Common Genetic Variants Amentioning
confidence: 99%
“…The ERBB3 gene encodes a protein in the EGFR family that functions as a heterodimer with other EGFR family members (87). The SNP rs2292239, located in intron 7 of ERBB3, is associated with T1DM, residual beta-cell function and metabolic control (88)(89)(90). Previous studies focused on this gene reported that it confers a risk for T1DM by modulating APC function to exert immunoregulatory effects (91).…”
Section: Erbb3mentioning
confidence: 99%
“…Previous studies focused on this gene reported that it confers a risk for T1DM by modulating APC function to exert immunoregulatory effects (91). A later study demonstrated that ERBB3 also affects beta-cell apoptosis (89). ERBB3 knockdown decreases basal and cytokineinduced apoptosis, but ERBB3 expression is downregulated by proinflammatory cytokines, indicating that this gene may participate in negative regulation by cytokines (89).…”
Section: Erbb3mentioning
confidence: 99%
See 1 more Smart Citation